ANALISIS DIMENSI PENGEMBANGAN WISATA CURUG SEWU KECAMATAN PATEAN KABUPATEN KENDAL - Muhamad Yudha Pratama; Retna Hanani (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2026)
The tourism sector plays an important role in regional development, including in Kendal Regency, where Curug Sewu serves as a leading natural tourism icon with significant potential, characterized by its multi-tiered waterfall and scenic natural landscape. However, its development has not been fully optimized due to limitations in facilities, accessibility, digital promotion, and management. This study aims to analyze the development of Curug Sewu based on the 4A dimensions (attraction, accessibility, amenities, and ancillary) and to identify the internal and external factors influencing its development. The research employs a descriptive qualitative approach through observation, interviews, and documentation. The findings indicate that the main attraction lies in its natural beauty, yet improvements are needed in accessibility, facility quality, and promotional strategies. Internal factors include tourism potential, human resources, infrastructure, management, and budget constraints, while external factors involve government policies, community participation, technological development, and stakeholder roles. Strengthening destination management, improving facilities, and optimizing digital promotion are necessary to achieve sustainable and competitive tourism development at Curug Sewu.